Mixed‐Phase Clouds and Precipitation in Southern Ocean Cyclones and Cloud Systems Observed Poleward of 64°S by Ship‐Based Cloud Radar and Lidar. Issue 8 (26th April 2021) - Alexander, S. P.; McFarquhar, G. M.; Marchand, R.; Protat, A.; Vignon, É.; Mace, G. G.; Klekociuk, A. R.
Abstract: Mixed‐phase clouds (MPCs), composed of both liquid and ice, are prevalent in Southern Ocean cyclones. A characterization of these clouds on fine vertical scales is required in order to understand the microphysical processes within these clouds, and for model and satellite evaluations over this region. We investigated three examples of cloud systems collected by ship‐mounted remote‐sensing instruments adjacent to East Antarctica at latitudes between 64°S and 69°S. These cases allow us to examine the properties of midlevel MPCs, with cloud tops between 2 and 6 km. Midlevel MPCs contain multiple layers of supercooled liquid water (SLW) embedded within ice during the passage of cyclones. SLW layers are capped by strong temperature inversions and are observed at temperatures as low as −31°C. Convective generating cells (GCs) are present inside supercooled liquid‐topped midlevel MPCs. The horizontal extent, vertical extent, and maximum upward Doppler velocity of these GCs were 0.6–3.6 km, 0.7–1.0 km, and 0.5–1.0 m s −1, respectively, and are consistent with observations from previous lower‐latitude studies. Ice precipitation is nearly ubiquitous, except in the thinnest clouds at the trailing end of the observed systems. Seeding of lower SLW layers from above leads to periods with either larger ice particles or greater ice precipitation rates. Periods of supercooled drizzle lasting up to 2 h were observed toward the end of two of the three cyclone systems. This supercooled drizzle turns into predominantly ice precipitation as the result of seeding by ice clouds located above the precipitating SLW layer. Key Points: Generating cells at the top of midlevel mixed‐phase clouds are commonly observed over the high‐latitude Southern Ocean Supercooled drizzle is present in two of the three cases examined here with phase changes following supercooled liquid layer seeding Seeding of single‐layer ice‐precipitating supercooled liquid clouds occurs in the trailing clouds of each system